2016
DOI: 10.1167/iovs.16-19286
|View full text |Cite
|
Sign up to set email alerts
|

Is Angiostatin Involved in Physiological Foveal Avascularity?

Abstract: PURPOSE. The primate central retina is characterized by an avascular fovea and well-defined perifoveal capillary plexus. Neither blood vessels nor their accompanying astrocytes enter the fovea during any stage of retinal development; a balance of angiogenic and angiostatic factors probably maintains foveal avascularity throughout life. The aim of this study was to identify potentially angiorepulsive factors involved in the development of the avascular primate retinal fovea. METHODS.Retinas of newborn, juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…According to the data of [37], MMP-2 and -9 are most frequently synthesized metalloproteinases in astrocytes. In addition, astrocytes express uPAR/uPA-plasminogen activating cascade [10]. It is worth noting that our data are in agreement with the report of Li [38] indicating that human glioma cell line BT325 can convert purified Pg to angiostatin-like fragments with molecular masses of 65, 60, and 58 kDa.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogsupporting
confidence: 92%
See 3 more Smart Citations
“…According to the data of [37], MMP-2 and -9 are most frequently synthesized metalloproteinases in astrocytes. In addition, astrocytes express uPAR/uPA-plasminogen activating cascade [10]. It is worth noting that our data are in agreement with the report of Li [38] indicating that human glioma cell line BT325 can convert purified Pg to angiostatin-like fragments with molecular masses of 65, 60, and 58 kDa.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogsupporting
confidence: 92%
“…Currently, numerous reports indicate that various cell types are able to gene rate angiostatins in relatively high amounts [8,9]. In the previous papers, angiostatins are described as constantly formed by several types of retina-resident cells [10]. So far, studies of angiostatins in brain tissue have been limited, with few exceptions [11][12][13], to effects of angiostatin-encoding genetic engineering constructions, which are expressed in the models of rat and human glioma cells developed for testing anti-angiogenic strategy for malignant brain tumor therapy [14,15].…”
Section: The Purpose Of the Present Study Was To Examine The Plasminomentioning
confidence: 99%
See 2 more Smart Citations
“…Böhm et al . reported that the foveola in humans and in rhesus monkeys displayed immunostaining for Tuj-1 49 . Tuj-1-positive cells in this area are probably ganglion cells, or their precursor.…”
Section: Discussionmentioning
confidence: 97%